Depression Screening on a Maternity Unit: A Mixed-Methods Evaluation of Nurses' Views and Implementation Strategies. (1st June 2014) - Segre, Lisa S.; Pollack, Lauren O.; Brock, Rebecca L.; Andrew, Jeana R.; O'Hara, Michael W.
<x xml:space="preserve">Abstract</x> Postpartum women often suffer clinically significant depressive symptoms, a problem addressed by nurse-delivered screening programs. In the past, success of these identification programs was measured in terms of screening rates; however, merely evaluating the screening rate does little to inform how to implement depression screening in clinical practice. This article describes the experiences of nurses in implementing depression screening on a maternity unit. We evaluate the practice qualitatively, by asking nurses to describe their screening strategies and their views about implementation, as well as quantitatively by assessing their screening rates and the number of women identified. Utilizing a framework of program evaluation, 20 maternity unit nurses completed qualitative assessments investigating their day-to-day experiences with this practice. To include the perspectives of nurses that declined to participate in qualitative assessments, 14 additional maternity unit nurses completed a brief survey assessing their views. We also assessed screening rates, defined as the number of women screened divided by the number eligible for screening. Maternity unit nurses viewed depression screening positively and were able to screen patients in relatively few steps, which they implemented using strategies they had developed themselves. Despite nurses' ongoing concern about finding time to screen, they achieved high screening rates and, with one exception, indicated they would opt to continue voluntarily. Depression screening on the maternity unit is feasible and embraced by attending nurses. The clinical strategies used to implement screening are extensively described and provide a basis for implementation in other settings that serve perinatal women.